Hubungan Tingkat Aktivitas Fisik dengan Fungsi Kognitif Lansia Wanita - Syifa Nur Ayuni; Dewi Dolifah; Delli Yuliana Rahmat (Jurnal Keperawatan Florence Nightingale, 2024)
The world population is currently in an aging population era which is the elderly contribute significantly to global population growth. The elderly are in the final phase of human life, where various changes have occurred, including physical, psychosocial, and cognitive functions. Physical activity is considered to inhibit the decline in cognitive function because it stimulates the production of brain-derived neurotropic factor (BDNF). This study aims to determine the relationship between the level of physical activity and the cognitive function of elderly women at Posbindu Melati II. The research method used was quantitative research with a correlational analytical design and a cross-sectional approach with a sample of 32 people. Data analysis test, where data was taken using the Global Physical Activity Questionnaire (GPAQ) and Mini Mental State Examination (MMSE) instruments. The research results showed that statistical tests with spearman rank showed (p <.001 smaller than the standard 0.05), which means there is a significant relationship between physical activity levels and cognitive function. The conclusion is that there is a relationship between the level of physical activity and cognitive function at Posbindu Melati II. Furthermore, elderly people are encouraged to do regular physical activity.